Analysis of heat stress on pollen development in Arabidopsis thaliana - Song, Yang (2017)
High temperature can have a serious impact on plant development; rising temperatures and environmental fluctuations mean that this is becoming an increasing problem for sustainable agriculture. Many studies have indicated that pollen development is very susceptible to high temperature (HT) stress, particularly during early development, and that the anther tapetum cell layer is extremely vulnerable, resulting in reduced fertility or complete male sterility (MS). In this project, Arabidopsis plants were stressed with 32°C HT during flowering and then assessed by microscopy for phenotypic changes to anther and pollen development, and subsequent reproductive development. The results indicate that the HT had a significant negative impact on plant reproduction, particularly during the stress treatment, with some recovery of fertility post HT. Samples of plant buds were divided into different growth stages and collected for analysis of fertility and for gene expression analysis. Several genes, which appear from available microarray data to be associated with HT stress and are also specifically expressed during tapetum development, were chosen to test for expression changes associated with temperature stress, both during and after HT stress. Phenotype analysis of insertional knockout mutants of these genes, both with and without HT stress, was used to assess their potential impact on resilience to temperature stress. Transcriptomic analysis of whole genome was conducted by RNA-seq in young (prior to polarized microspore stage) and old buds (from polarized microspore stage to pollen mitosis) isolated from HT-stressed and non-stressed Arabidopsis Ler plants. This has identified a set of HT specific genes that are differentially expressed in different HT period treated plants. The anther tapetum serves to regulate pollen development and is critical in the production of the pollen wall. It goes through a defined process of programmed cell death (PCD) to facilitate transfer of pollen wall materials onto the developing pollen grains. Disturbance of the timing or progression of this PCD process, for example by heat stress frequently results in male sterility. Four GFP reporter constructs that have been used as markers during ovule PCD analysis were tested for expression during pollen development and particularly focusing upon the stages of tapetal PCD. These reporter genes showed different stage specific expression during anther development. They have now been introgressed into a number of Arabidopsis male sterile mutants that show PCD-related defects, including ms1, ams and myb26 male sterile mutants. The F1 generation of these showed similar GFP expression to the parent plants, however the homozygous male sterile F2 generation plants appeared to show different patterns of GFP expression. Two of them (BFN1 and CEP1) are expressed in the anther tapetum during the stages of tapetum PCD. Expression analysis suggests that HT-stress affects the expression of BFN1 and CEP1, which may be linked to abnormal degeneration of the tapetum under HT-stress.